2010
DOI: 10.2478/v10001-010-0016-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of injuries and reporting of accidents among health care workers at the University Hospital of the West Indies

Abstract: Objectives: This study investigated the knowledge, awareness and practices of health care workers towards universal precautions at the University Hospital of the West Indies. The study also examined the prevalence of injuries experienced by health care workers, as well as incidence of accidents and compliance with post-exposure prophylaxis. Materials and Methods: A cross sectional survey was conducted in September and October 2007. A 28-item self-administered questionnaire was provided to two hundred health ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
56
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 24 publications
10
56
2
Order By: Relevance
“…our results higher than those reported by Duerink et al 9 (44%) at two teaching hospitals on the island of Java, Luo et al 10 and abdulraheem et al 11 observed that only 50% of the HCWs had knowledge of universal precautions. The results of Vaz et al 12 were near to our results (64.0%). our result was lower than those reported by Danchaivijitr et al 13 who reported that 94.9% of medical doctors in Thailand had good knowledge of standard precautions.…”
supporting
confidence: 62%
“…our results higher than those reported by Duerink et al 9 (44%) at two teaching hospitals on the island of Java, Luo et al 10 and abdulraheem et al 11 observed that only 50% of the HCWs had knowledge of universal precautions. The results of Vaz et al 12 were near to our results (64.0%). our result was lower than those reported by Danchaivijitr et al 13 who reported that 94.9% of medical doctors in Thailand had good knowledge of standard precautions.…”
supporting
confidence: 62%
“…This study revealed that occupational cut injury occurred in 75% of HCWs. This is higher than similar studies in the University Hospital of the West Indies and Georgia (occupational cut injury prevalences of 43.5% 22 and 38% 12 respectively), and is higher than that reported from eight major health facilities in Kampala, Uganda 23 and in a tertiary care academic health organization of North India 24 (prevalence of 17% and 9.9% respectively). This finding could be attributed to the fact that being a tertiary care hospital there is a high workload.…”
Section: -22 Not For Citation Purposescontrasting
confidence: 50%
“…Following these measures have crucial affects on the safety of both patients and HCWs, but unfortunately, despite the simplicity and clarity of these measures, compliance level with standard precaution among nurses and NIs is still low. [14,15] Compliance is the level of precision and constancy in following prescribed standard protocols to achieve the desired outcomes. [16] Various factors can influence the level of compliance including cultural, economical and social factors.…”
Section: Introductionmentioning
confidence: 99%